Workshop on Making Coconut Milk Ice Cream as a Business Opportunity for PKK Women in Sungai Itik Village - Panjaitan, Ruqiah Ganda Putri; Septiani, Uray Rina; Rahmah, Adnin; Lorensa, Sisi Marda; Mandasari, Junika; Tumiang, Kresensia Imakulata; Setiyawati, Neni; Yenni, Yenni; Reza, Muhammad; Nurhuda, Nurhuda; Irvandi, Dede (International Journal of Public Devotion, 2024)
Ice cream is a kind of frozen dish that has a sweet, cold and mellow taste. The raw material for making ice cream generally uses milk, but the use of milk fat from cow's milk in making ice cream can be replaced with vegetable fat derived from plants such as coconut. The purpose of this workshop activity is to provide new knowledge or innovation for the development of processed food sourced from the natural potential of Sungai Itik Village which can be used as a business opportunity by PKK women. The method of implementing this workshop activity was carried out in three stages, namely the first stage of field survey and preparation of activity plans. The second stage of socialization is conveying the designs that have been made to the village. The third stage is the implementation of activities based on the activity plan that has been prepared. The results obtained from the workshop activities of PKK women gained new knowledge about making coconut milk ice cream and were able to sell the products that had been produced.